233 GI Pathology Residency Education: Barrett Esophagus (BE) Biopsy Evaluation. (11th January 2018) - Assarzadegan, Naziheh; Casler, Vektra; Esnakula, Ashwini; Gonzalo, David Hernandez; Harrell, Danielle; Huang, Yanfei; Kim, Jong; Nasri, Elham; Patel, Vatsal; Xie, Hao; Liu, Xiuli
Abstract: Background: Incidence of Barrett esophagus (BE) neoplasia has increased, and its management has changed dramatically. Assessment of dysplasia in BE is a diagnostic challenge in gastrointestinal pathology practice and residency education. This study aims to examine the diagnostic skills of pathology residents in interpreting BE mucosal biopsies. Method: Sixty-two cases of BE mucosal biopsies (38 negative for dysplasia, eight low-grade dysplasia, 10 high-grade dysplasia, one cancer) were included in the study. The slides were reviewed by seven pathology residents for diagnosis and recognition of histologic features, including nuclear enlargement, hyperchromasia, nuclear stratification, nuclear pleomorphism, loss of nuclear polarity, abnormal mitosis, dystrophic goblet cell, architectural complexity, and surface maturation. The resident's interpretation was compared to the final diagnosis in the pathology report. Interobserver agreement (IOA) was determined using the Fleiss kappa coefficient (K) analysis. Results: There was fair IOA among seven pathology residents (kappa 0.32). Agreement between each resident and the final diagnosis in the pathology report varied significantly (kappa –0.15 to 0.76). The degree of agreement with the final diagnosis was not related to the length of residency training. Of the evaluated histologic features, nuclear pleomorphism is recognized with moderate IOA (kappa 0.42), followed by loss of nuclear polarity, nuclear enlargement, and hyperchromasia (kappa 0.36, 0.34, 0.21, respectively). The remaining examined features have poor to slight IOA. Conclusion: This study reveals significant interobserver variability in BE neoplasia diagnosis among pathology residents regardless of PGY level. This calls for providing individualized education to trainees. Further, this study identifies surface maturation and architectural complexity as difficult features to be recognized by pathology residents.